A randomized controlled effectiveness trial of training strategies in cognitive processing therapy for posttraumatic stress disorder: Impact on patient outcomes. (November 2018) - Monson, Candice M.; Shields, Norman; Suvak, Michael K.; Lane, Jeanine E.M.; Shnaider, Philippe; Landy, Meredith S.H.; Wagner, Anne C.; Sijercic, Iris; Masina, Tasoula; Wanklyn, Sonya G.; Stirman, Shannon Wiltsey
Abstract: This randomized controlled hybrid implementation/effectiveness trial aimed to compare the impact of three different models of training and consultation by examining the PTSD treatment outcomes achieved by therapists who were learning a front-line recommended psychotherapy for posttraumatic stress disorder (PTSD), Cognitive Processing Therapy (CPT; Resick, Monson, & Chard, 2017). Therapists ( N  = 134) were randomized into one of three conditions after attending a standard CPT training workshop: No Consultation with delayed feedback on CPT fidelity, Standard Consultation involving discussion and conceptualization of cases without session audio review, and Consultation Including Audio Review, which included a review of segments of audiorecorded CPT sessions. Across all training conditions, the patients treated by these therapists ( N  = 188) evidenced statistically significant reductions in PTSD symptoms, ( d  = −0.95 to −1.78), comorbid symptoms and functioning ( d  = −0.27 to −0.51). However, patients of therapists in the Standard Consultation condition (ΔPTSD = - 19.64, d  = −1.78) experienced significantly greater improvement than those in the No Consultation condition (ΔPTSD = - 10.54, d  = −0.95, ΔDEV = 6.30, ΔParms = 2, p  = .043). This study demonstrates that patients who receive evidence-based psychotherapy for PTSD in routine care settings can experience significant symptom improvement. Our findings also suggest that to maximize patient benefit, therapist training should include consultation, but that audio review of sessions during consultation may not be necessary, at least for structured protocols. Implications for implementation, including the reduction of burden and cost of post-workshop support, are discussed. Highlights: Compared outcomes of CPT when delivered by therapists trained using 3 different post-workshop support strategies. In all conditions, patients with PTSD experienced significant PTSD symptom reduction. Patients of therapists who received a standard form of consultation experienced significantly more improvement. Review of audio recorded therapy sessions may not be necessary for effective consultation of highly-structured treatments.